Stable Superwetting Surface Prepared with Tilted Silicon Nanowires - Meng, Xiangman; Zhou, Ailin; Wang, Bo; Chen, Yu; Tang, Yun-Hui; Yan, Hui (Nano-Micro Letters, 2016)
Large-scale uniform nanostructured surface with superwettability is crucial in both fundamental research and engineering applications. A facile and controllable approach was employed to fabricate a superwetting tilted silicon nanowires (TSNWs) surface through metal-assisted chemical etching and modification with low-surface-energy material. The contact angle (CA) measurements of the nanostructured surface show a large range from the superhydrophilicity (the CA approximate to 0°) to superhydrophobicity (the CA up to 160°). The surface becomes antiadhesion to water upon nanostructuring with a measured sliding angle (α) close to 0°. Moreover, the fluorinated TSNWs surface exhibits excellent stability and durability because strong chemical bonding has been formed on the surface.